CLINICAL PERSPECTIVE OF AVARAN - Jagruti Chaple; Sonali Chalakh (International Journal of Applied Ayurved Research, 2015)
Avarana is one of the least understood concepts among the basic mechanisum of ayurvedic fundamentals. Avarana is one of the mechanisms mentioned in the science of Ayurveda to explain the pathogenesis of diseases, peculiarly due to the vitiation of vata . But now a day in clinical practice, we are not focusing on this area for diagnosis as well as management strategies. In Ayurveda, the vitiation of a srotus is essential for the manifestation of each and every disease .In any disease or disorder, the nidana or causative factors will lead to dosha dushti, the vitiated dosha gets accumulated in the particular srotuses, leading to the manifestation . If a Possible condition arises, the disease commences. The Various reasons of vitiation of srotas are also explained .The difference in the pathology of the srotuses leads to the different diseases.